Cardiac and Locomotor Responses to Acute Stress in Signal Crayfish Pacifastacus leniusculus Exposed to Methamphetamine at an Environmentally Relevant Concentration - Ložek, Filip; Kuklina, Iryna; Grabicová, Kateřina; Kubec, Jan; Buřič, Miloš; Randák, Tomáš; Císař, Petr; Kozák, Pavel (International journal of environmental research and public health, 2020)
Methamphetamine (METH), a central nervous system stimulant used as a recreational drug, is frequently found in surface waters at potentially harmful concentrations. To determine effects of long-term exposure to environmentally relevant levels on nontarget organisms, we analysed cardiac and locomotor responses of signal crayfish Pacifastacus leniusculus to acute stress during a 21-day exposure to METH at 1 μg L-1 followed by 14 days depuration. Heart rate and locomotion were recorded over a period of 30 min before and 30 min after exposure to haemolymph of an injured conspecific four times during METH exposure and four times during the depuration phase. Methamphetamine-exposed crayfish showed a weaker cardiac response to stress than was observed in controls during both exposure and depuration phases. Similarly, methamphetamine-exposed crayfish, during METH exposure, showed lower locomotor reaction poststressor application in contrast to controls. Results indicate biological alterations in crayfish exposed to METH at low concentration level, potentially resulting in a shift in interactions among organisms in natural environment.
Keywords: fyziologický stres; aquatic environment; pollution; invertebrates; Female; Methamphetamine; zvířata; predator–prey relationship; methamfetamin; Stress, Physiological; ženské pohlaví; Male; behaviour; Water Pollutants, Chemical; severní raci; Animals; Astacoidea; mužské pohlaví; illicit drug; chemické látky znečišťující vodu